ACADEMIC SUPERVISION TO IMPROVE TEACHER'S CAPABILITY IN ARRANGING ASSESSMENT ADMINISTRATION THROUGH DOCUMENT REVIEW AND GUIDANCE DURING THE COVID-19 PANDEMIC - Makmur (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine how the planning, implementation, and follow-up steps of academic supervision by supervisors improve teacher competence in preparing assessment administration. This research employed an action research design. Data were analyzed using comparative descriptive and quantitative techniques. The results indicated that academic supervision effectively improved teacher competence in arranging assessment administration. The average scores of teacher competence in preparing assessment administration were 69.11 in the initial condition, 74.78 in the first cycle, and 78.11 in the second cycle. The increase from the initial condition to the first cycle was 5.67, and from the first cycle to the second cycle was 3.33. It can be concluded that the implementation of academic supervision positively affects teachers’ ability to prepare assessment administration.